HIV Risk Perception in Relation to Impulsivity and Consideration of Future Consequences: A Review - Singh, Balkar (International Journal of Psychosocial Rehabilitation, 2013)
erception word is taken from the Latin word “percipare‟ which means „to take hold‟ or to „comprehend‟. Perception refers to the way the world looks, sounds, feels, taste, or smells. In other words, perception is whatever a person experiences. The three dimensional world is perceived through our sense organs and processed to provide the basis for interaction with the external world.